Brain death: reflections - D'Onofrio, Felice (Medicina e Morale, 1986)
The realisation of cardiac transplantation in Italy too, alongside its undoubtedly positive aspects, however, raises a number of fundamental problems that cross over from the purely technical-scientific field into the ethical-ontological one, which cannot be ignored, let alone underestimated.